2020
DOI: 10.1371/journal.pone.0243912
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and psychometric evaluation of the French version of the Gilles de la Tourette Syndrome Quality of Life Scale (GTS-QOL)

Abstract: Introduction The Gilles de la Tourette Syndrome–Quality of Life Scale (GTS-QOL) is a self-rated disease-specific questionnaire to assess health-related quality of life of subjects with GTS. Our aim was to perform the cross-cultural adaptation of the GTS-QOL into French and to assess its psychometric properties. Methods The GTS-QOL was cross-culturally adapted by conducting forward and backward translations, following international guidelines. The psychometric properties of the GTS-QOL-French were assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In parallel of our work (that began in 2012), two Italian and English versions of the GTS-QOL for children and adolescents, named the C&A-GTS-QOL, were developed and validated in 2013 and 2016 [ 45 , 46 ]. The five-factor structure of the GTS-QOL-French-Ado differs from the four-factor structure of the Italian version and the six-factor structure of the English-language version of the C&A-GTS-QOL [ 45 , 46 ] and from the six-factor structure of the GTS-QOL-French for adults [ 14 ]. Compared to the Italian version [ 45 ], the GTS-QOL-French-Ado has one additional subscale, the ‘Social’ subscale, and the other four subscales are not composed of exactly the same items.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In parallel of our work (that began in 2012), two Italian and English versions of the GTS-QOL for children and adolescents, named the C&A-GTS-QOL, were developed and validated in 2013 and 2016 [ 45 , 46 ]. The five-factor structure of the GTS-QOL-French-Ado differs from the four-factor structure of the Italian version and the six-factor structure of the English-language version of the C&A-GTS-QOL [ 45 , 46 ] and from the six-factor structure of the GTS-QOL-French for adults [ 14 ]. Compared to the Italian version [ 45 ], the GTS-QOL-French-Ado has one additional subscale, the ‘Social’ subscale, and the other four subscales are not composed of exactly the same items.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in the Italian and English-language versions of the C&A-GTS-QOL [ 45 , 46 ], the ‘Psychological’ subscale of the GTS-QOL-French-Ado does not include items related to social domain grouped together in the ‘Social’ subscale. A ‘Social’ subscale also exists in the GTS-QOL-French for adults [ 14 ]. Several studies found impaired social functioning and peer relationship problems in youths with GTS [ 4 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations